High Specific Capacity Thermal Battery Cathodes LiCu2O2 and LiCu3O3 Prepared by a Simple Solid Phase Sintering - Wang, Yan; Bai, Xintao; Luo, Zeshunji; Fu, Licai (Frontiers in Chemistry, 2020)
The thermal battery has been designed to be active at high temperature to satisfy storage life and large capacity for storage and emergency power. The development of thermal battery with high specific energy requires that the cathode has high thermal stability and excellent conductivity. Here, the semiconductor material Li–Cu–O compounds LiCu2O2 and LiCu3O3 are synthesized by a simple solid-phase sintering technique, which is simpler than the traditional synthesis process. The thermal decomposition temperatures are 680°C and above 900°C, respectively. This work first applies the Li–Cu–O compounds to the thermal battery. With a cutoff voltage of 1.5 V, the specific capacities of LiCu2O2 and LiCu3O3 are 423 and 332 mA h g−1. Both the decomposition temperature and specific capacity are higher than in the commercial FeS2 and CoS2, especially LiCu2O2. This work affords an alternative of the cathode materials for high specific capacity thermal battery.